In vitro and in vivo characterisation of Listeria monocytogenes outbreak isolates. (January 2020) - Stratakos, Alexandros Ch; Ijaz, Umer Zeeshan; Ward, Patrick; Linton, Mark; Kelly, Carmel; Pinkerton, Laurette; Scates, Pam; McBride, Jane; Pet, Ioan; Criste, Adriana; Stef, Ducu; Couto, Jillian M.; et al.
Abstract: Listeriosis is an important food-borne disease responsible for high rates of morbidity and mortality. L. monocytogenes has been the cause of several foodborne outbreaks and its ability to adapt and survive in a wide range of environmental conditions makes eradication difficult. Many L. monocytogenes strains are avirulent but have the ability to increase their virulence if exposed to environmental stresses. The aim of this study was to explain the observed increase in virulence of outbreak L. monocytogenes isolates by using phenotypic assays and whole genome sequencing. Four L. monocytogenes isolates from sweetcorn and one isolate from a raw milk (control) were sequenced and characterised using a range of phenotypic assays. The four L. monocytogenes sweetcorn isolates displayed a significant increase for in vitro adhesion and invasion of epithelial cells compared to the control isolate. They also showed a higher level of colonisation of the liver and spleen in vivo . In addition, the four L. monocytogenes isolates displayed an increased ability to form biofilms, resist heat stress and resist a combination of antimicrobials. Investigation of the genomes of the four L. monocytogenes sweet corn isolates identified Single Nucleotide Polymorphisms (SNPs) in genes, which may have a role in the observed phenotypes characteristic of these strains, particularly in response to survival properties within the environment or in terms of virulence. We highlight the importance of combining whole genomic sequencing with phenotypic characterisation as a key element in the investigation of outbreaks of foodborne pathogens. Highlights: Listeria monocytogens outbreak isolates show increased virulence in vitro . Genotype and phenotype changes lead to higher in vitro adhesion and invasion. Increased liver and spleen colonisation in vivo for all food isolates.